Lycium barbarum Polysaccharide Improves Bipolar Pulse Current-Induced Microglia Cell Injury Through Modulating Autophagy. Issue 3 (March 2015) - Bie, Man; Lv, Yi; Ren, Chaoran; Xing, Feiyue; Cui, Qi; Xiao, Jia; So, Kwok Fai
Blindness and visual impairments are heavy loads for modern society. Visual prosthesis is a promising therapy to treat these diseases. However, electric stimulation (ES)-induced damage of the optic nerve and adjacent cells are problems that must not be overlooked. In the current study, we aimed to investigate the effects of ES on cultured microglia cells and the potential protective mechanisms from a natural compound Lycium barbarum polysaccharide (LBP). Cellular injuries were induced by 9 mA bipolar pulse current in BV-2 cells for 15 min. Treatment with LBP alone or in association with either autophagic inhibitor 3-MA or autophagic agonist rapamycin was preadded for 2 h before the ES challenge. After that, morphological and molecular changes of the cells were measured at 2 h or 6 h postchallenges. We found that ES induced evident morphological and pathological changes of BV-2 cells, including oxidative stress, inflammation, and apoptosis. Pretreatment with LBP significantly attenuated these injuries with enhanced endogenous autophagy. When cellular autophagy was inhibited or enhanced by corresponding drug, the protective properties of LBP were partly inhibited or maintained, respectively. In addition, we demonstrated that ERK and p38 MAPK exerted diversified roles in the protection of LBP against ES-induced cellular damages. In conclusion, LBP improves bipolar pulse current-induced microglia cell injury through modulating autophagy and MAPK pathway.